2022
DOI: 10.3390/cancers14051336
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Intervention—A Panacea for Cancer Treatment?

Abstract: The molecular mechanism of action and the individual influence of various metabolic pathways related to metformin intervention are under current investigation. The available data suggest that metformin provides many advantages, exhibiting anti-inflammatory, anti-cancer, hepatoprotective, cardioprotective, otoprotective, radioprotective, and radio-sensitizing properties depending on cellular context. This literature review was undertaken to provide novel evidence concerning metformin intervention, with a partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 198 publications
0
22
0
Order By: Relevance
“…In 2013 over 100 clinical trials designed to assess the potential benefits of metformin in the treatment of cancer were listed on the NIHH Clinical Trials government web site [245]; as of May 2022 the number now exceeds 380 with breast cancer featuring dominantly but also trials involving the following cancers: endometrial and ovarian, head and neck squamous cell, multiple myeloma, thyroid, and lymphocytic leukemia. Several systematic reviews and meta-analyses have concluded that there was a reduction in risk of mortality and developing cancer in the range of 14 to >30%, with, in some analyses, increases in risk in subjects treated with sulfonylureas, insulin, and alpha glucosidase inhibitors when compared to treatment with metformin [227,235,[246][247][248][249][250][251]. However, as reported by DeCensi et al, (2010) the use of metformin is not always associated with a significant benefit as seen for colon, breast and prostate cancers where there was no evidence for a reduction in risk [247].…”
Section: Epidemiological Studies and Clinical Trialsmentioning
confidence: 99%
“…In 2013 over 100 clinical trials designed to assess the potential benefits of metformin in the treatment of cancer were listed on the NIHH Clinical Trials government web site [245]; as of May 2022 the number now exceeds 380 with breast cancer featuring dominantly but also trials involving the following cancers: endometrial and ovarian, head and neck squamous cell, multiple myeloma, thyroid, and lymphocytic leukemia. Several systematic reviews and meta-analyses have concluded that there was a reduction in risk of mortality and developing cancer in the range of 14 to >30%, with, in some analyses, increases in risk in subjects treated with sulfonylureas, insulin, and alpha glucosidase inhibitors when compared to treatment with metformin [227,235,[246][247][248][249][250][251]. However, as reported by DeCensi et al, (2010) the use of metformin is not always associated with a significant benefit as seen for colon, breast and prostate cancers where there was no evidence for a reduction in risk [247].…”
Section: Epidemiological Studies and Clinical Trialsmentioning
confidence: 99%
“…It has also been indicated that activation of AMPK by metformin can have a pleiotropic effect (Zang et al 2004 a, b; Vasamsetti et al 2015 ). Additionally, various studies have shown that treatment with metformin is effective in heart diseases, including cardiotoxicity (Kuburas et al 2022 , O’Neill et al 2022 , Park, Park et al 2022 ), heart failure (Benes et al 2022 , Buczyńska et al 2022 , Hendawy et al 2022 ), atrial fibrillation (Bai et al 2019 ; Liu et al 2020 , Zhou et al 2022 ), coronary heart disease (Hua et al 2018 ; Luo et al 2020 ).…”
Section: Metformin and Therapeutic Goalsmentioning
confidence: 99%
“…Metformin has been used for the treatment of metabolic diseases and cancer 56 . The main mechanism described for metformin as an antitumor agent is the activation of the AMPK signaling pathway 56 .…”
Section: Mul1 In Pathological Conditionsmentioning
confidence: 99%
“…Metformin has been used for the treatment of metabolic diseases and cancer 56 . The main mechanism described for metformin as an antitumor agent is the activation of the AMPK signaling pathway 56 . In addition, previous studies have shown that metformin decreases Akt activation in several cancer cells.…”
Section: Mul1 In Pathological Conditionsmentioning
confidence: 99%
See 1 more Smart Citation